Formaldehyde Oxidizing Enzymes and Genetically Modified Yeast Hansenula polymorpha Cells in Monitoring and Removal of Formaldehyde - Sibirny, Vladimir; Demkiv, Olha; Sigawi, Sasi; Paryzhak, Solomiya; Klepach, Halyna; Korpan, Yaroslav; Smutok, Oleh; Nisnevich, Marina; Gayda, Galina; Nitzan, Yeshayahu; Puchalski, Czesław; Gonchar, Mykhailo (IntechOpen, 2011)
None